Total sugars soluble in Carya illinoinensis, balance between key phenological stages - Concilco-Alberto, Ernesto; Valenzuela-Núñez, Luis Manuel; González-Torres, Anselmo; Briceño-Contreras, Edwin Amir; García-De la Peña, Cristina; Reyes-Carrillo, José Luis (Ecosistemas y Recursos Agropecuarios, 2022)
Total Soluble Sugars (ATS) are essential carbohydrates in growth, metabolism and survival mechanisms in stress conditions in decidous trees. The objective was to quantify ATS in Carya illinoinensis in different organs and phenological stages, in this specie and to be able to have an approximation to the adaptive capacity of the specie. Samples were obtained from trees during vernalization, bud differentiation and flowering stages. The ATS concentrations in root, stem, branch, shoot, leaf and fruit were determined by spectrophotometry. Differences in ATS concentration were detected between organs and between phenological stages, statistically significant differences were recorded in stem, branch and shoot, presenting the highest values in the vernalization and differentiation of buds. The root showed the higher concentration in ATS remaining available throughout the production cycle.